Copper-catalyzed asymmetric conjugate addition of alkylzirconium reagents to cyclic enones to form quaternary centers. - Roth, P; Sidera, M; Maksymowicz, R; Fletcher, S (Nature Publishing Group, 2014)
This protocol describes the catalytic asymmetric formation of all-carbon quaternary centers--a distinctive feature of many natural products and pharmaceuticals--via conjugate addition of alkylzirconium reagents to a tertiary enone. This methodology uses alkenes as starting materials and enables the incorporation of functional groups. The alkylzirconium reagent is generated in situ by mixing the alkene with the Schwartz reagent. The alkylzirconium is added to a solution containing a copper-ligand complex, and then the enone is added to the mixture. The addition of pent-4-en-1-ylbenzene to 3-methyl-2-cyclohexenone is detailed herein as a generic example. This procedure works at room temperature (∼25 °C), and it is scalable to at least 1.5 g. The setup of the reaction takes 3-5 h and the reaction goes to completion within 4-20 h.